2388. Efficacy of Humanized Cefiderocol Exposures Over 72 Hours Against a Diverse Group of Gram-Negative Isolates in the Neutropenic Murine Thigh Infection Model. (26th November 2018) - Stainton, Sean; Monogue, Marguerite; Tsuji, Masakatsu; Yamano, Yoshinori; Echols, Roger; Nicolau, David P
Abstract: Background: Previous pharmacodynamic (PD) assessments conducted over a 24 hours dosing period have revealed that cefiderocol humanized exposures produced predictable bacterial kill against MDR Gram-negatives with MICs ≤4 mg/L. Our current aim was to evaluate the sustainability of cefiderocol in vivo activity over 72 hours against MDR pathogens. A. baumannii (AB, n = 4), P. aeruginosa (PSA, n = 2), K. pneumoniae (KP, n = 4) and E. coli (EC, n = 2) displaying cefiderocol MICs of 0.5–16 mg/L were used in the neutropenic murine thigh model. Methods: Mice received either humanized exposures of cefiderocol equivalent to the clinical dose [2g q8h 3h inf.] or cefepime (FEP) reflective of a 2g q8h 3h inf or vehicle. Efficacy was determined as the change in log CFU at 24, 48 and 72h compared with 0 hours controls. MICs were determined on organisms recovered from both the control and treatment animals. Results: In AB, PSA and Enterobacteriaceae (EB) displaying MICs 0.5–8 ( n = 9), infected mice given cefiderocol showed reductions of 0.5–3 log CFU at 72 hours. The killing profile observed among these 9 isolates followed a similar trend, demonstrating an initial reduction in bacterial burden at 24 hours which was sustained at 48 hours and 72 hours. As expected based on the PD profile of cefiderocol, no killing was seen with the AB isolate (MIC = 16). While cefiderocol exposure resulted in the killing of the FEP-resistant phenotype of the EB, mice receiving FEP displayed growth similar to controls. Infection with the remaining 2 organisms (EC 462, MIC = 1; KP 531, MIC = 4) resulted in a cumulative increase in bacterial burden over the study duration resulting in 1–2 logs growth following cefiderocol exposure over 72 hours. Retest MICs revealed an increase (≥2 dilutions) compared with control in only 1 animal (1/54 samples or 1.8%) observed in EC 462 at 72 hours. Additional samples from this group (2/3) remained unchanged throughout the study duration. Importantly, the retest MIC for this sample did not exceed the MIC of 4 mg/L. Conclusion: These data show that for isolates demonstrating kill at 24 hours, cefiderocol efficacy was unchanged over the 72 hours treatment period. Despite the MDR profile of the pathogens tested their phenotypic profile remained largely unchanged and adaptive resistance during therapy was not observed. Disclosures: M. Tsuji, Shionogi & Co., Ltd.: Employee, Salary. Y. Yamano, Shionogi & Co., Ltd.: Employee, Salary.